Unveiling the determinants of work-related stress in the policing occupation - Mohd Zin, Md. Lazim; Ibrahim, Hadziroh; Mohd Noor, Mohd Hafiz; Ahmad, Umair (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2019)
The present study attempts to provide empirical evidence on the relationship between workload, working conditions, role conflict and job stress among the Royal Malaysian Police (RMP) Personnel. A survey among 178 RMP from six departments at one XYZ Police District in Selangor was conducted. Self-reported measures for all variables were used to obtain data pertaining to determinants of job stress. Multiple regression was employed to investigate three hypotheses that postulated significant positive relationships between workload, working conditions, role conflicts and job stress.The regression results found that workload and working conditions have positive relationships with job stress. However, role conflict did not significantly influence job stress. Plausible justifications for the relationships between workload and working conditions and job stress were discussed. The study provides a foundation for discussing both theoretical and managerial aspects of policing occupation